Cena newsa. Nowe internetowe formy dziennikarstwa; ich potencjał biznesowy - Zimnak, Marek (Value of news. New forms of internet journalism and businness potential, 2007)
The article covers two lines of interest: New forms of Internet journalism as well as their business potential. New media have to pickup the gauntlet - they must earn for their living. Meanwhile the costs of adequate promotion are rapidly increasing and the costs of technical infrastructure are equally high. The audience of news consumers is used to pay for paper, also for - let’s say – traditional electronic media as radio or tv. They are not used to pay for news reached by new channels of communication. In spite of all written above the tendency seems to be obvious - news by internet has become very serious informing channel that should be well recognized by sociologists, economists as well as by media profesionalists.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Nauki Humanistyczne (11); 2007; nr 1188, s. 281-292